ANTI-CORRUPTION IN UZBEKISTAN: THE ROLE OF PERSONAL RESPONSIBILITY - Mamadaliyeva Feruza Asrorovna (Modern American Journals, 2025)
This study explores the role of personal responsibility and moral values in combating corruption, emphasizing the complementary role of individual ethics and institutional reforms. Using Uzbekistan as a case study, the research examines how civil society organizations (CSOs) influence ethical awareness, promote citizen participation, and challenge informal norms. The study relies on document analysis and literature review to demonstrate that sustainable anti-corruption efforts require moral commitment from individuals, supported by community engagement and civic education. Findings reveal that CSOs play a critical role in shaping a culture of integrity and reinforcing the moral obligations of both citizens and public officials.
Keywords: Corruption, Personal Responsibility, Moral Values, Civil Society Organizations (CSOs), Uzbekistan, Ethical Behavior, Anti-Corruption Reform, Civic Engagement, Institutional Accountability, Public Ethics